GLOBALIZATION OF REGIONAL CONFLICTS: A FUTURE WAR FOR THE UPPER KARABAKH - TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2009)
Globalization in international relations is perhaps best understood in terms of increased interdependence in the international system. This interdependence manifests itself in both economic and military affairs. Since World War II, the United States has been the leading force behind “globalizing” processes: as economic interdependence leads toward more open markets, and military interdependence makes global affairs more peaceful, it has been in the vital interest of Washington to rid the world of isolationist and militarily autarkic powers.1 With increased interdependence regional conflicts also have become politically globalized. No regional conflict today remains isolated to a particular region despite the fact that very few of them directly affect power hierarchy in the international system. Regional conflicts in part acquire their global significance due to a spread of the phenomenon loosely understood as “soft power.”2 Since the dominant powers in today’s world are either liberal democracies (the United States, the United Kingdom, France, etc.) or trying to play the democratic game (Russia, China, India, etc.), the concepts associated with democratic ideals have become the major currency in soft power transactions. Therefore, regional actors have to pay attention to public opinion and cultural sensitivities prevalent in dominant global powers even though these powers may not be directly affected by regional conflicts. Soft power of public opinion and ideals of international justice and freedom may well push and/or allow hard power to step in to quell or mediate by force a protracted conflict, and this could have disastrous consequences for one or both parties involved in a regional dispute